Japanese Language Interest on Nursing Students toward Intention to Work in Japan at Stikes Pemkab Jombang - Pepin Nahariani; Kikis Widya Ratna; Kolifah Kolifah; Iin Noviana; Shanti Rosmaharani (Jurnal Ners, 2019)
Introduction: In Indonesia, the working prevalence of nurses was that 95% worked in the country and 5% were working abroad. The government provides opportunities for nurses who want to work in Japan through networking (Indonesia Japan Economic Partnership Agreement). However, there isn’t a lot of interest due to the lack of knowledge of the Japanese language. This study aimed to analyze the Japanese language related to the nursing students’ interest concerning working in Japan.Methods: The design of the study was correlational research with a cross-sectional approach which was conducted between May 31st and June 1st, 2016. The population consisted of nursing Bachelor’s program students and the population totaled 41; the samples totaled as many as 37. The data collection used Japanese observation test scores and questionnaires.Results: The results showed that most of the 75.6% got a good score (B). Nearly half (48.6%) of them were intending to work in Japan and 2.7% got great scores, also with the intent to work Japan. Based on the test results, the statistical value = 0.798 that the ρ value> α (0.05).Conclusion: This means that there is no correlation between the Japanese language and the nurse’s working interest related to Japan. The recommendation in this study is the implementation of an active Japanese language course. Further research should analyze the factors that affect the interests of Indonesian nurses when it comes to working in Japan.